Pertumbuhan Bibit Tanaman Manggis (Garcinia mangostana L.) Setelah Inokulasi dengan Berbagai Galur Agrobacterium rhizogenes1 - , Lizawati; Roedhy Poerwanto; , Sobir; Iman Rusmana; Tri Muji Ermayanti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Growth of mangosteen essentially depends on its root system.  Therefore, it needs technology to obtain stringer mangosteen root system.  The use of Agrobacterium rhizogenes bacterium is an alternative.  The objectives of this experiment were : 1) to find the effective strain of A. rhizogenes bacterium for inoculation of mangosteen seedling root, 2) to find the best inoculation method for inducing mangosteen seedling root.  The materials used in this experiment were ; mangosteen fruit and A. rhizogenes collection from Puslit Biotechnology LIPI Cibinong-Bogor.  The experiment was arranged in completely randomized design with two factorial treatments.  The first factor : 11 strains A. rhizogenes (ATCC-15834, ATCC-8196, R-1000, 07-20001, A4, A4-J, 509, 510, 511, MAFF 01-1724, and control), the second factor : 2 inoculation methods (cutting and dipping).  The results showed that A. rhizogenes  of ATCC-15834, 509, 07-20001, A4, and R-1000 increased stem diameter, plant height, leaf number, lateral and tertiary root number, better than ATCC-8196, MAFF 01-1724, 510, 511, A4-J, and control.  Cutting root method of inoculation resulted in higher live plant percentage compared to dipping root method.   Key words :  Agrobacterium rhizogenes, Garcinia mangostana, inoculation